Imidazole-based phenanthroline derivatives induce DNA damage-mediated apoptosis to suppress hepatocellular carcinoma - Jie LIN; Shuyuan ZHOU; Hairong XIAN; Weiming CHEN; Yifan ZHANG; Weiwei ZHANG; Zhihong GUAN; Wenjie MEI (KeAi Communications Co., Ltd., 2022)
Objective: This study focused on designing and subsequently screening novel phenanthroimidazole derivatives with activity as potential inhibitors of hepatocellular carcinoma. Methods: We synthesized a series of phenanthroimidazole derivatives and their molecular structures were characterized by ESI-MS and 1H NMR. The anti-tumor activity was evaluated using the MTT assay. The potential mechanism of anti-tumor activity based on DNA-damage-mediated apoptosis was analyzed by flow cytometry, immunofluorescence, and comet assay. Additionally, the anti-angiogenic activity was assessed by transgenic zebrafish. Furthermore, in vivo biodistribution of the compound was studied using a nude mice xenograft model. Results: The screening results for anti-tumor activity revealed that the compounds, especially 2, exhibited promising restrain activity against the growth of HepG2 cells with an IC50 value of 0.68 µM. Further studies showed that 2 can accumulate in the mitochondria of HepG2 cells, decreased the mitochondrial membrane potential, induce DNA damage and apoptosis of cells. Moreover, it was also discovered that 2 can inhibit the formation of neovascularization, which was confirmed by the decrease in ISV angiogenesis of zebrafish after being incubated with 2, as well as the decrease in the number and length of tubes formed in HUVECs cells. Besides, in vivo distribution and metabolism studies show that 2 is rapidly distributed in the whole body and accumulated in the tumor tissue of BALB/c mice. Conclusion: Taken together, this type of phenanthroimidazole derivatives, especially 2, will be developed to be potent inhibitors against the growth of HepG2 cells through anti-angiogenesis and apoptosis based on mitochondrial-dependent pathways in the near future.